Dynamic framing in the communication of scientific research: texts and interactions - Davis, Pryce; Russ, Rosemary S. (Wiley, 2015)
The fields of science education and science communication share the overarching goal of helping non-experts and non-members of the professional science community develop knowledge of the content and processes of scientific research. However, the specific audiences, methods, and aims employed in the two fields have evolved quite differently and as a result, the two fields rarely share findings and theory. Despite this lack of crosstalk, one theoretical construct—framing—has shown substantial analytic power for researchers in both fields. Specifically, both fields have productively made use of the fact that when people approach situations or texts in the world, they do so with a sense of “what is going on here” that guides their actions and sense-making in that situation. In this article, we examine the dynamics of how interactions between scientists, reporters, members of the general public, and various texts give rise to in-the-moment frames that shape each actors interpretation of scientific research. In doing so we couple science communication literature's focus on framings within and across texts with science education's focus on dynamic framing in interactions. We present a case study that follows a single piece of scientific research from scientist to reporter to the general public. Through semi-structured clinical interviews, video-based observation, and qualitative content analysis, we demonstrate that changes in science knowledge as it moves along the pathways of science communication are the aggregate result of dynamic moment-to-moment framings dispersed over people and interactions. The complexity and nuance of the story presented here have implications for how each field—science communication and science education—conceptualizes the process by which the public comes to knowledge of science.